2020
DOI: 10.1177/0265407520940415
|View full text |Cite
|
Sign up to set email alerts
|

Who sees opportunity to help? A prospective study on adolescents’ detection of intervention opportunities in situations of sexual and dating violence

Abstract: Adolescent bystanders (i.e., witnesses to violence) can prevent sexual and dating violence among their peers and create a safer social environment if they detect the opportunity. The current study prospectively examined the association of demographic (i.e., age, gender, sexual orientation), psychosocial (i.e., knowledge, rape myth acceptance, victim empathy), and behavioral (i.e., binge drinking) factors with bystander opportunity detection in situations regarding sexual and dating violence among adolescents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Reactive bystander behavior is Journal of Interpersonal Violence more complex and may be something that happens in smaller groups (2-3 peers), or when a bystander is alone without peers, which would suggest that there is less chance to observe the behavior and less strong effects of networks. Research with adults suggests that one-third of sexually violent events occur in the presence of a bystander (Lukacena et al, 2019;Planty, 2002), and adolescents report high levels of opportunity to help across the continuum of peer sexual violence (Waterman et al, 2020). Bystanders are present in almost two-thirds of emotional and physical dating violence victimization, again in mainly adult samples (Black et al, 2008;Hamby et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive bystander behavior is Journal of Interpersonal Violence more complex and may be something that happens in smaller groups (2-3 peers), or when a bystander is alone without peers, which would suggest that there is less chance to observe the behavior and less strong effects of networks. Research with adults suggests that one-third of sexually violent events occur in the presence of a bystander (Lukacena et al, 2019;Planty, 2002), and adolescents report high levels of opportunity to help across the continuum of peer sexual violence (Waterman et al, 2020). Bystanders are present in almost two-thirds of emotional and physical dating violence victimization, again in mainly adult samples (Black et al, 2008;Hamby et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Results of one recent study showed variation in bystander intervention across gender and sexual minority identifying participants and that gender- and sexual-minority participants reported more opportunities to intervene (Hoxmeier, Mennicke, et al, 2020) compared to cisgender and heterosexual participants. Another recent study found that sexual minority girls detected more intervention opportunities than did boys or sexual majority girls (Waterman et al, 2020). Future research in these populations is necessary to replicate these findings and additionally examine potential differences in attitudes, subjective norms, PBC, and behavioral intention regarding bystander intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize also that our findings only apply to those who reported having at least one opportunity in the past 12 months to intervene across all of the BI items. We do not know why some students had an opportunity to engage in one or more of the bystander behaviors and others did not—although the individual’s lifestyle routine activities likely shape those opportunities (Waterman et al, 2020). It is also possible that some students did have an opportunity to intervene but did not perceive the situation as necessitating intervention for a number of reasons, such as attitudes toward the potential victim or perpetrator (see, e.g., Butler et al, 2017; Pugh et al, 2016; Waterman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%